Responsible tourism: Pangkor island residents’ perception, practices and impact on quality of life / Mohamad Daim Darson - Darson, Mohamad Daim (2013)
Island is a branch of tourism products that attract anyone including tourist and investor who seek for the concept of “sun, sand, beach and wind”. Island tourism sector regarded as a vital economic generator, creating business and job offers and improving income. However, this mechanism affects the economic, socio-cultural and environment particularly in the aspect of quality of life (QOL). Therefore, to sustain the development in line with the constructive effects, many governments introduced the concept of responsible tourism. In comparison with other literature, this study focuses its scope to the local residents rather than a tourist. Hence, this research looks at the perceptions of the local residents towards tourism development, impact on quality of life and responsible tourism practice. Self-administered questionnaires distributed to the Pangkor Islands’ local community from four main tourist areas namely Pasir Bogak, Teluk Dalam, Teluk Nipah and Pangkor Jetty. Using quantitative approaches the experiences of one hundred and forty three local residents were tapped. Through a series of descriptive and inferential analyses, some useful understandings or analysts on the issues of interest revealed. Finding clearly revealed that resident’ perceptions towards tourism development, responsible tourism and perceived benefits have positively influenced residents’ quality of life. Economic attributes among the most contributors that give significant impact to the quality of life compared to ecology and socio-cultural. In line with the empirical relationship, interaction between perceived benefits and responsible tourism possessed the significant effect towards the study. The results also contribute to the future literature especially in responsible tourism concept in Malaysia which needs further exploration.